Anti-Proliferative Potential of Fucoidan on Human Prostate Cancer Cells - Prakash, Bhawana (Auckland University of Technology, 2016)
Fucoidan is a sulphated polysaccharides from seaweed. In the present study, commercial crude and pure fucoidan from F. vesiculosus (CCF, CPF; purchased from sigma), crude fucoidan from New Zealand U. pinnatifida extracted at AUT (ACF) and commercial pure fucoidan from U. pinnatifida (UPF; purchased from sigma) were investigated for their antiproliferative effect on human prostate cancer cell lines (PC-3 and DU-145; which are analogous to androgen-independent cancer cells). Two types of bioassays were employed to test the anticancer potentials of CCF, ACF, UPF and CPF. The MTT cell proliferation assay was employed to determine the viability of cells after treatment with various concentration of fucoidans, and the apoptosis assay using Flow Cytometer to determine the proportion of apoptotic sub-G1 hypodiploid cells. Results reveal that crude fucoidan from either of the species (CCF and UPF) were more effective in inhibiting growth of prostate cancer cells in a time and dose dependent manner than pure forms of fucoidan (CPF and UPF). Once the antiproliferative effect of fucoidans were evaluated, the mechanism behind this effect was elucidated by flow cytometric analysis of apoptosis. Crude fucoidan were found to induce more cell death in a dose dependent manner after 72 hours of treatment. Cytotoxic effect of various fucoidan tested in this study were analysed on normal cells (HEK-293) as well. It was demonstrated that CCF was most toxic as it inhibited the growth of normal cell to the greatest extent (IC50 value, 268.2 ?g/ml; sub-G1, 27.40%), whereas ACF was comparatively less cytotoxic (IC50 value, 958.4 ?g/ml; sub-G1, 11.73%) than CCF and exhibited lower apoptosis inducing activity on normal cells. Even though ACF was less capable of inhibiting the growth of prostate cancer cells in comparison to CCF (the most effective), owing to its lesser toxicity towards normal cells, ACF would be a more apt option to be investigated further for its activity against prostate cancer. Thus this study highlights that fucoidan form New Zealand U.pinnatifida might have therapeutic potential for advanced prostate cancer treatment with milder side effect.
Keywords: Seaweed; Prostate cancer; Apoptosis assay; Mtt assay